2017
DOI: 10.1016/j.zemedi.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centre evaluation of accuracy and reproducibility of planar and SPECT image quantification: An IAEA phantom study

Abstract: Accurate quantitation of activity provides the basis for internal dosimetry of targeted radionuclide therapies. This study investigated quantitative imaging capabilities at sites with a variety of experience and equipment and assessed levels of errors in activity quantitation in Single-Photon Emission Computed Tomography (SPECT) and planar imaging. Participants from 9 countries took part in a comparison in which planar, SPECT and SPECT with X ray computed tomography (SPECT-CT) imaging were used to quantify act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…An overview of the most recently applied methods for SPECT/ CT quantification with therapeutically used radionuclides, different phantom geometries, volumes, camera vendors, reconstruction methods, and the related accuracies has been provided by Tran-Gia et al (24). Table 1 shows only publications with reported accuracies of less than 10% (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Image Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the most recently applied methods for SPECT/ CT quantification with therapeutically used radionuclides, different phantom geometries, volumes, camera vendors, reconstruction methods, and the related accuracies has been provided by Tran-Gia et al (24). Table 1 shows only publications with reported accuracies of less than 10% (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Image Quantificationmentioning
confidence: 99%
“…In an international multicenter calibration and standardization trial, Zimmerman et al (25) found by using calibrated 133 Ba sources that SPECT/CT systems showed better reproducibility and better accuracy than planar imaging. The results for SPECT/CT were almost operator-independent.…”
Section: Image Quantificationmentioning
confidence: 99%
“…In contrast, image-domain correction techniques try to restore spilled-out counts on the basis of anatomic information or predetermined experimental findings, such as by multiplication with a spheric recovery coefficient (11,12) or more organ-specific correction factors obtained in anthropomorphic, 3dimensional (3D) printed phantoms (13)(14)(15). Although many efforts have been made to standardize quantitative SPECT/CT imaging (5,6,16,17), the lack of a widely accepted and routinely applied standardization still impedes a comparison of quantitative SPECT/ CT acquisitions across different clinical centers and different manufacturers. This, in turn, obstructs the conduction of multicentric or longitudinal studies for validating and optimizing the therapeutic use of new radiopharmaceuticals (18).…”
mentioning
confidence: 99%
“…verabreichten Radiopharmazeutikums für die Dosimetrie beruht auf der quantitativen Bildgebung mittels serieller Gamma-Kamera-Scans und mindestens einem SPECT(/CT). Die Dosimetrie, die auf quantitativen 3-dimensionalen Daten basiert, ist erheblich genauer [3]. Darüber hinaus kann eine inhomogene Organakkumulation des Radionuklids nachgewiesen und ggf.…”
Section: Die Etablierte Methode Zur Bestimmung Der Biokinetik Desunclassified